Um jogo sem regras explícitas: investigação sobre o lugar das técnicas e das tecnologias nas leituras da fotografia publicitária - Lima, Cristina Schroeder (Universidade do Vale do Rio dos Sinos, 2013)
This dissertation has as its wide preoccupation understand the impact of the association of techniques and digital technologies to the productive processes of advertising photography through and from actual photographs put into circulation by advertising in the last years. In this sense, the questions that motivated the reflections developed here concern the contemporary photographic statute and, in particular, of advertising photography. To face such problematic in a operational mode, we chose to analyze the finalist photographs at Prêmio Conrado Wessel – Advertising Photography Category, between the years of 2003 and 2006, a selection legitimated by the players involved in the practice of advertising photography, since the referred prize consolidates itself as a place where conceptions, limits and values inherent to this field so fluid and porous are consolidated and affirmed by the institution itself and the agents mobilized by it. In this empirical context, it was sought to comprehend and define the differentiation that advertising, through its practices, suggests to the concept of photography; elaborate the place of technologies and digital manipulation techniques in the construction of photographs produced for ads considering possible readings; to formulate tensions between the use of these techniques and technologies and our understanding and reading of photographic images in the advertising context; to seek for inferences about definitions of advertising photography out from the semio-technical relations and the reading and productive processes of advertising photography. In the image analysis it was proceeded initially a “internal” reading, of technical- iconographic character, and thereafter it was employed “external” resources, specially interviews, with the purpose of returning the photographs to its original advertising context.
Keywords: Fotografia digital; Fotografia publicitária; Prêmio fundação Conrado Wessel; Imaginário contemporâneo; Digital photography; Advertising photography; ACCNPQ::Ciências Sociais Aplicadas::Comunicação